2020
DOI: 10.1017/jns.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

StudentKost: a cross-sectional study assessing college students’ diets: reason for concern?

Abstract: College students constitute a significant proportion of the young adult population in Norway. They are in their reproductive years, which is of interest regarding diet and preconception health. Our objective was to assess young college students’ diet and nutrient intake in relation to national dietary recommendations and assess the probability of inadequate micronutrient intake for both genders using the Nordic Nutrition Recommendations, and also to evaluate its consequences on preconception health and create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…In this study, the reported use of iron supplements was low (9%), of which 12 participants were female vegans and 5 participants were male vegetarians. However, supplement use in our study is similar to the low use of iron supplements reported among female (6% took iron supplements every day) and male (4% did the same) Norwegian students [46]. Low iron supplement use was also reported in the German study among vegan and lacto-ovo vegetarians, with fewer than one-fifth of the participants being iron supplement users [40].…”
Section: Iron Supplement Usesupporting
confidence: 86%
“…In this study, the reported use of iron supplements was low (9%), of which 12 participants were female vegans and 5 participants were male vegetarians. However, supplement use in our study is similar to the low use of iron supplements reported among female (6% took iron supplements every day) and male (4% did the same) Norwegian students [46]. Low iron supplement use was also reported in the German study among vegan and lacto-ovo vegetarians, with fewer than one-fifth of the participants being iron supplement users [40].…”
Section: Iron Supplement Usesupporting
confidence: 86%
“…The analyses for this paper are based on dietary data from the cross-sectional survey StudentKost (10) . The overall aim of StudentKost was to assess students' diet in relation to official dietary guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Participants had to answer every question to complete the questionnaire, with self-reported height and weight being the only voluntary information. Satisfactory testretest reproducibility and fair relative validity of the FFQ assessed against a 7-day food record have been documented (10) . Median test-retest Spearman's r correlations for energy and nutrients was r = 0•85, ranging from r = 0•56 for vitamin D to r = 0•93 for Ca.…”
Section: The Questionnairementioning
confidence: 98%
“…13 In addition, our recent study of the diet of Norwegian students identified a reason for concern, showing low diet quality compared with recommendations, with a more deficient diet among men than women. 14 Students constitute a large proportion of the preconception population in Norway. Hence, there is an opportunity for being better prepared for one’s health and the health of the next generation.…”
Section: Introductionmentioning
confidence: 99%
“…National surveys suggest significant opportunities for dietary improvements in the intake of fruits, vegetables, whole grains, nuts/seeds, fish and milk as well as reduced intake of processed meat and salt among Norwegian young adults 13. In addition, our recent study of the diet of Norwegian students identified a reason for concern, showing low diet quality compared with recommendations, with a more deficient diet among men than women 14. Students constitute a large proportion of the preconception population in Norway.…”
Section: Introductionmentioning
confidence: 99%